2020
DOI: 10.1002/anie.202011466
|View full text |Cite
|
Sign up to set email alerts
|

A Simple Homoleptic Gallium(I) Olefin Complex: Mimicking Transition‐Metal Chemistry at a Main‐Group Metal?

Abstract: The earth-metal olefin complex [Ga I (COD) 2 ] + [Al-(OR F) 4 ] À (COD = 1,5-cyclooctadiene; R F = C(CF 3) 3) constitutes the first homoleptic olefin complex of any main-group metal accessible as a bulk compound. It is straight forward to prepare in good yield and constitutes an olefin complex of a main-group metal that-similar to many transition-metalsmay adopt the + 1 and + 3 oxidation states opening potential applications. Crystallographic-, vibrational-and computational investigations give an insight to th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
9
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 14 publications
(9 citation statements)
references
References 72 publications
0
9
0
Order By: Relevance
“…Hence, [pf] (H atoms omitted for clarity) and QTAIM analysis, i. e. the Laplacian of the electron density, of the bonding interaction between Ga and the C=C double bonds. [54] considering the significant stabilization of the ns 2 -electron pair (n = 4,5) in cationic complexes outlined previously, the introduction of a positive charge represents a promising pathway to overcome this hurdle. In fact, [Ga(PhF) 2 ][CHB 11 Cl 11 ] was reported to be accessible in high yield via spontaneous H 2 -elimination from the [H 2 Ga III (PhF) 2 ][CHB 11 Cl 11 ] complex.…”
Section: Towards Application Of Low-coordinate M I Saltsmentioning
confidence: 99%
See 2 more Smart Citations
“…Hence, [pf] (H atoms omitted for clarity) and QTAIM analysis, i. e. the Laplacian of the electron density, of the bonding interaction between Ga and the C=C double bonds. [54] considering the significant stabilization of the ns 2 -electron pair (n = 4,5) in cationic complexes outlined previously, the introduction of a positive charge represents a promising pathway to overcome this hurdle. In fact, [Ga(PhF) 2 ][CHB 11 Cl 11 ] was reported to be accessible in high yield via spontaneous H 2 -elimination from the [H 2 Ga III (PhF) 2 ][CHB 11 Cl 11 ] complex.…”
Section: Towards Application Of Low-coordinate M I Saltsmentioning
confidence: 99%
“…). [18,[52][53][54] Figure 4. a) Frontier orbitals of the [Ga{P( t Bu) 3 } 2 ] + -complex as calculated on PBE0-D3BJ/def2-TZVPP//BP86-D3BJ/def2-SVP level of DFT (isovalue of 0.09 a.u.).…”
Section: On the Nature Of Low-coordinate M I Complexesmentioning
confidence: 99%
See 1 more Smart Citation
“…Krossing and co-workers successfully isolated [Ga(COD)2] + complex in high yields. [187] The cationic Ga + is coordinated to four double bonds of the two COD ligands in a pseudo-tetrahedral arrangement. Theoretical studies showed there is no back-bonding to the COD ligands, implying a dominant electrostatic interaction of Ga + and COD.…”
Section: Group 13 Complexesmentioning
confidence: 99%
“…Mechanistic routes for the cationic Ga- or Ag-catalyzed propargylic substitution reaction were postulated (Scheme ). It was thought that the metal could coordinate with the hydroxyl of 13 (see 14 ) or both the alkyne and the hydroxyl to form pi-coordinated 15 , which corresponds to the need for a soft Lewis acid. , Since trifluoroborate salts did not serve as good nucleophiles in this reaction, the hydroxyl group of the boronic acid might be playing a role in the reaction mechanism. Recruitment of the boronic acid by the metal could then produce adduct 17 .…”
mentioning
confidence: 99%